Pro.NET framework with the base class library : understanding the virtual execution system and the common type system - Villela, Roger (Apress, 2019)
Learn about the fundamentals and inner workings of the Common Type System (CTS) and the Virtual Execution System (VES) of the Common Language Runtime (CLR) and how they relate to the Base Class Library (BCL) from the perspective of the execution environment. The author first gives an introduction to the .NET Framework and describes the architectural and engineering resources required when implementing the .NET Framework on any platform. Next, you will learn about the BCL and understand how to work with system structures including the fundamental built-in types system.array and system.string. You will then learn about the VES along with its methods and functionality. Further, you will go through the Common Intermediate Language (CIL), Assembly Manifest, and versioning. You will also learn how to design and implement libraries in detail by creating a .NET class library. After reading this book, you will understand .NET Framework features, as well as details about the core functionalities of the VES and elements of the CTS. You will: Discover details of the Common Type System (CTS) Work with the Virtual Execution System (VES) See the importance of correct use of fundamental built-in managed types Carry out good programming practice in a managed environment Implement a .NET class library.